Empowerment of Farmer Community Group in Sampali Village Together with Students of Agriculture Faculty Medan Area University in Barangan Banana Plants Development with Tissue Culture Banana Seeds,Suckers and Applications of Mycorrhiza - Suswati Suswati; Sumihar Hutapea; Asmah Indrawaty (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Sampali Village is an agricultural area that is very suitable for banana planting. Various types of bananas found in the village include Barangan, Kepok, Molen, Raja and banana Nangka . Banana shoots from harvested mother plants are used for development in new areas. Banana seedlings from the suckers appear healthy, but often these suckers die after 1-2 months of planting in new areas. This is because these bananas have been infected with fungal pathogen wilt caused by Fusarium oxysporm f. sp cubense and Ralstonia syzygii subsp. celebesensis causes of blood diseases. Both of these pathogens are the main cause of the low quality of banana seeds. The use of low-quality banana seedlings (sapling sources), high pest and disease attacks are the factors causing the reduced amount of banana planting land which results in low banana production in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency. Banana farmer groups in the village of Sampali have never used and planted banana seedlings that were propagated by tissue culture. The objectives of the activity were: 1. Socialization and practice of propagation of banana seedlings from sucker . Mycorrhizal inoculant application when planting seedlings in a polybag. To increase the knowledge of farmer group members and also the  students of Agricukture Faculty,Universitas Medan Area the learning of banana propagation techniques is carried out in vitro at the Balai Benih Induk Hortikultura, Gedung Johor Medan . The method used to solve the above problems is the provision of material, the practice of making banana seedlings through the propagation of tillers and a visit to the Balai Benih Induk Hortikultura, Gedung Johor Medan. At the end of the activity, an increase in the knowledge and skills of participants in providing quality banana seeds is the source of banana propagation in the village Sampali